AN ASSESSMENT OF THE IMPACT OF ICT IN CREATING AWARENESS OF GENDER EQUALITY AMONG ST YOUTHS IN SOME SELECTED DISTRICTS WITHIN ABUJA MUNICIPAL AREA COUNCIL (AMAC), NIGERIA. - Sani, Azizatu Oiza (The Gender Truth Journal, 2024)
Gender equality has emerged as a paramount focus for the international community since the dawn of the 21st century. This critical issue, prominently featured in the United Nations Millennium Development Goals (MDGs) continues to be a cornerstone of the current Sustainable Development Goals (SDGs), with countries worldwide striving to achieve gender parity by 2030. In Nigeria, efforts to address gender disparities have gained momentum in recent years. Nigeria’s National Gender Policy, adopted in 2006 and revised in 2021, aims to eliminate discriminatory practices across various sectors. Some progress has been made in areas such as increasing girls’ access to education and improving women’s representation in governance. Despite efforts to bridge the gender gaps, gender inequality persists. The study assessed the role of Information Communication Technologies (ICTs) in shaping the perceptions of young people on gender equality, in selected districts within Abuja Municipal Area Council (AMAC). The study adopted the survey method with a questionnaire as the instrument of data collection. The study sampled 100 youths aged 15-40. Findings reveal that youths are very familiar with the concept of gender equality which promotes equal rights and opportunities for all genders. The study also found that Facebook, Twitter, and Instagram are the most effective ICT platforms for gender equality awareness. However, there exists the challenge of misinformation about gender issues, and difficulty in verifying information sources. The study recommends the need for the Nigerian government to further invest in digital infrastructure, and the integration of ICT in formal education to enhance gender equality awareness among youths.